A multiple drug allergy syndrome, multiple drug intolerance syndrome and/or allergic drug reaction with multiple immune reactants - Ana Maria Abreu Velez; Vickie M. Brown; Michael S. Howard (Our Dermatology Online, 2016)
Background: Adverse drug reactions (ADR), multiple drug allergy syndrome (MDAS) and multiple drug intolerance syndrome (MDIS), are very common in the clinical practice worldwide due to an aging population. Case report: Here we describe a 61 year old Caucasian female, who presented complaining of large, tense bullae on her right anterior arm; the bullae had been present for one week, with pruritus. The patient was taking multiple medications. The patient presented with multiple large, tense blisters and scattered, smaller blisters on her legs and axillae. Materials and Methods: Biopsies for hematoxylin and eosin (H&E) examination, direct immunofluorescence (DIF) and immunohistochemistry (IHC) analysis were performed. The H&E staining demonstrated diffuse, moderate epidermal spongiosis, with a subepidermal blister. Lymphocytes and eosinophils were present within the blister lumen and around superficial dermal blood vessels, hair follicles and sweat glands. Notably, blood vessels and lymphatics had altered shapes, many being narrowed, twisted and or dilated. DIF showed significant deposits of fibrinogen, Complement/C3c and IgA around the dermal vessels; some reactivity was also present at the basement membrane zone of the skin, as well as around dermal skin appendices. Of great interest was the reactivity seen with anti-human fibrinogen against some dermal cell junctions. IHC staining showed the presence of mainly CD4 and BCL-2 positive cells around skin appendices, with a few CD8 positive cells also present. Cyclooxygenase-2 was also very positive around the dermal blood vessels, as well as within cells of the dermal inflammatory infiltrate. The dermal lymphatics and dermal blood vessels appeared dilated, demonstrated by staining for D2-40/podoplanin and von Willembrand factor. Conclusion: Adverse drug reactions and multiple drug allergy syndrome have several overlapping features; the spectrum of immunopathologic and histopathologic features are not fully established. Our case contributes to our knowledge of some of these features. In the authors' experience, we have noticed that the hallmark of these reactions is the prevalence of strong deposits of fibrinogen in several vessels and dermal skin appendices. In addition, we have noted positivity on some types of dermal cell junctions. MDAS, MDIS and ADRs represent examples of how to categorize adverse, simultaneous reactions to multiple classes of chemically unrelated drugs.